PENGARUH MANAJEMEN KELAS TERHADAP MOTIVASI BELAJAR SISWA DI SDN 2 DAWAGUNG TASIKMALAYA - Siti Aulia Syaudia; Rahmatul Fajri, Laili; Doni Nugraha (Program Studi Manajemen Pendidikan Islam, 2024)
This research aims to determine the effect of classroom management on student learning motivation at SDN 2 Dawagung Tasikmalaya. This research uses quantitative correlational methods. Data collection was carried out using the technique of distributing questionnaires and documentation studies. Informants included the principal, teachers and students of grades 4, 5 and 6 of SDN 2 Dawagung Tasikmalaya. Data analysis was carried out using quantitative analysis techniques which included data collection, data testing, data presentation, and drawing conclusions. Meanwhile, to check the validity of the data, researchers used validity and reliability tests with the IBM SPSS version 26.0 MacOS application. The results of this research indicate that the level of classroom management tendencies and student learning motivation at SDN 2 Dawagung Tasikmalaya is in the medium category. In the determination